2010
DOI: 10.1002/elan.200900559
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode Sensing of Adenosine/Adenosine‐5′‐triphosphate with Fast‐Scan Cyclic Voltammetry

Abstract: Adenosine and adenosine-5'-triphosphate (ATP) are important extracellular signaling molecules. Here, we studied adenosine and ATP using fast-scan cyclic voltammetry at carbon-fiber microelectrodes. Although ATP and adenosine have similar oxidation potentials, ATP oxidation current was highly dependent on buffer pH and divalent cation concentrations but adenosine current was not. Therefore, they can be distinguished by adding a divalent cation chelator or calibrating electrodes at different pH values. The enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…We have previously shown that our electrode is twice as sensitive to adenosine as ATP (35), three times more sensitive than AMP, and does not detect inosine (31). Pharmacological data presented in this paper show that ectonucleotidase inhibitors have no effect on high-frequency stimulated release, providing evidence that ATP is not the analyte being detected.…”
Section: Resultsmentioning
confidence: 98%
“…We have previously shown that our electrode is twice as sensitive to adenosine as ATP (35), three times more sensitive than AMP, and does not detect inosine (31). Pharmacological data presented in this paper show that ectonucleotidase inhibitors have no effect on high-frequency stimulated release, providing evidence that ATP is not the analyte being detected.…”
Section: Resultsmentioning
confidence: 98%
“…ATP has the same oxidation reaction as adenosine, and the traces are similar except that carbon-fiber microelectrodes are more sensitive to adenosine. 16 , 18 , 19 Dopamine has a peak at 0.6 V and is shown as a control for comparison purposes. 34 36 …”
Section: Resultsmentioning
confidence: 99%
“… 16 Adenosine poses a specific challenge due to its relatively high E 0 (∼1.30 V), 17 so a switching potential of 1.45–1.50 V is necessary with FSCV. 16 , 18 , 19 Adenosine is a neuromodulatory molecule found in the brain 20 22 and is neuroprotective during conditions of ischemia 23 , 24 and hypoxia. 25 , 26 Detection of adenosine using FSCV 3 , 16 , 18 is beneficial for understanding how adenosine functions on the subsecond to second time scale.…”
mentioning
confidence: 99%
“…The lower sensitivity for ATP is likely due to poor adsorption because of the negative charge or steric hindrance of the phosphate groups that prevent the adenine moiety from being properly aligned for oxidation. 38 …”
Section: Resultsmentioning
confidence: 99%